The impact of antibodies to human glycoprotein CD4 and gamma-interferon on the t-cell immunity and the cytokine levels in patients co-infected with HIV/HCV during the antiretroviral therapy - A. V. Strygin; A. M. Docenko; A. O. Strygina; E. I. Morkovin; V. I. Petrov (Медицинский вестник Юга России, 2017)
Objective: This work was to estimate the influence of antibodies to human glycoprotein CD4 and IFN-γ on the T-cell immunity and the cytokine levels in patients with HIV and HIV/HCV during the standard antiretroviral therapy. Materials and methods: Randomized clinical trial in parallel groups. 4 groups were included: patients with HIV receiving ART (20) or ART and antibodies (AB) (19) for 3 months; patients with HIV/HCV, receiving ART (17) or ART and AB (20) for 3 months. The obtained data included: CD3+, CD4+, CD8+ cell count; IFN-γ, IL-2 and IL-4 concentrations; HIV viral load. Results: The significant increase of CD4+ cell number and IFN-γ were found in patients receiving ART and antibodies. These changes were followed with more significant decline in the viral load. Conclusion: The antibodies to human glycoprotein CD4 and IFN-γ added to standard ART increased the CD4+ cell count and IFN-γ levels in patients with HIV/HCV, followed by the trend to increase the number of patients with viral load >50 ml-1. Thus, the administration of ART supplemented with antibodies to human glycoprotein CD4 and IFN-γ resulted in the increase of antiviral immunity. Further clinical trials in HIV or HIV patients with co-infections could be recommended.